Prostanoid stimulation of anion secretion in guinea-pig gastric and ileal mucosa is mediated by different receptors. - Bunce, K. T. (1990)
1. The receptors that mediate stimulation of anion secretion by prostanoids in isolated preparations of guinea-pig gastric and ileal mucosa have been compared by use of selective prostanoid agonists and antagonists. 2. In gastric mucosa, the relative potency of agonists suggested that the control of anion secretion in this tissue was complex and may be mediated by EP2, EP3, and TP receptors. A role for TP receptors was confirmed with the TP-selective antagonist AH23848 which inhibited short circuit current responses to the TP receptor agonist U-46619 with a pA2 value of 8.44 but was without effect on responses to prostaglandin E2 (PGE2) or the EP selective agonist, sulprostone. 3. In ileal mucosa, the relative potency of agonists differed from that observed in gastric mucosa and was consistent with the view that anion secretion in this region of intestine was controlled by DP and EP2 receptors. 4. These studies suggest that anion secretion in gastric and ileal mucosa is controlled by different prostanoid receptor subtypes and so provide important information for the design of prostanoids which may protect gastric mucosa and that are free from side effects such as diarrhoea.